Vahram Vardanyan, Spiritual Screams in Silence, Yerevan, Publishing House “Asoghik”, 2020, 152 pages - Minasyan, Edik; Tovmasyan, Rubik (History and Culture, 2022)
The review refers to Vahram Vardanyan’s work “Spiritual Screams in Silence”. This is the story of a family, representatives of which lived in several villages of the Taron region. During the Genocide, the 59 members of this family appeared in exile, as a result of which it settled in Kakavadzor village of Talin region. The work presents the documentary material, which is at the disposal of Vahram Vardanyan and the memoirs that the author heard from the surviving members of this family.
Keywords: Vahram Vardanyan; Spiritual Screams in Silence; Armenian Genocide; Verin Marnik; Taron region; Kakavadzor village of Talin region; memoir; history of the Big Family